2017
DOI: 10.1371/journal.pone.0182185
|View full text |Cite
|
Sign up to set email alerts
|

Child contact management in high tuberculosis burden countries: A mixed-methods systematic review

Abstract: Tuberculosis (TB) remains a leading cause of morbidity and mortality worldwide. Considering the World Health Organization recommendation to implement child contact management (CCM) for TB, we conducted a mixed-methods systematic review to summarize CCM implementation, challenges, predictors, and recommendations. We searched the electronic databases of PubMed/MEDLINE, Scopus, and Web of Science for studies published between 1996–2017 that reported CCM data from high TB-burden countries. Protocol details for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 50 publications
2
109
1
3
Order By: Relevance
“…In our study, <5‐year‐old contacts that were second‐degree relatives of index cases and contacts of a smear‐negative index case were less likely to start IPT. This is in line with a systematic review of child contact management that found children who were offspring of the index case and those who slept in the same room of the index case to be more likely to start IPT . The risk of TB transmission is related to contact intensity and infectiousness of the index case, and both health staff and parents may have a lower risk perception in such instances.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, <5‐year‐old contacts that were second‐degree relatives of index cases and contacts of a smear‐negative index case were less likely to start IPT. This is in line with a systematic review of child contact management that found children who were offspring of the index case and those who slept in the same room of the index case to be more likely to start IPT . The risk of TB transmission is related to contact intensity and infectiousness of the index case, and both health staff and parents may have a lower risk perception in such instances.…”
Section: Discussionsupporting
confidence: 80%
“…Existing literature from South Africa and other settings has documented nurse fatigue with excessive recordkeeping [17][18][19]. Furthermore, a recent systematic review examining child TB contact management in high burden settings found a lack of tools to support documentation was a common barrier to successful management of child TB contacts [20]. Our ndings suggest the provision of simple tools that are designed with nurse buy-in may enhance uptake, and in this instance facilitate the provision of TPT.…”
Section: Discussionmentioning
confidence: 75%
“…A limited number of studies have explored provider attitudes regarding TB prevention in children in a high TB burden setting in-depth (13). In this qualitative study, we found interest and commitment among healthcare providers in Lesotho to improve CCM.…”
Section: Discussionmentioning
confidence: 77%